2016
DOI: 10.21082/akp.v10n1.2012.31-56
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Kebijakan Perbenihan Kentang

Abstract: Policy on potato seed system is based on the eagerness to boost quality seed production and distribution, and to encourage the farmers to use high quality seed. Existing official rules of potato seed industry are intended to produce quality potato seed through official standard operation procedure. There is an act, however, tends to limit foreign capital ownership in the horticulture seed industry that discourages foreign investors. In terms of regional autonomy, the regional governments have more roles in see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
5
0
7
Order By: Relevance
“…Bondowoso Regency is one of the strategic areas of agricultural development and buffer zone of regional food [15]. Bondowoso Regency is also one of six chosen regencies in East Java as national potato seed developer area [16]. The researcher is more specifically focusing on Ijen District because potato commodity is only cultivated at that place in Bondowoso Regency.…”
Section: Methodsmentioning
confidence: 99%
“…Bondowoso Regency is one of the strategic areas of agricultural development and buffer zone of regional food [15]. Bondowoso Regency is also one of six chosen regencies in East Java as national potato seed developer area [16]. The researcher is more specifically focusing on Ijen District because potato commodity is only cultivated at that place in Bondowoso Regency.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that G0 seeds were produced by government institutions as well as collaboration between universities and farmer groups. For example in West Java, the G0 was generated by IVegRI Lembang, then distributed or sold by BBI, PD Hikmah, and Pesantren Darul Fallah Bogor (Sayaka & Hestina, 2011;Sayaka et al, 2012). Meanwhile, the G0 in East Java was produced by AIAT, BBI province, and Horticulture and Crops Seed Supervision and Certification Office in Indonesia called Balai Pengawasan dan Sertifikasi Benih Tanamanan Pangan dan Hortikultura (BPSBTPH) of East Java.…”
Section: Harvesting and Post-harvestmentioning
confidence: 99%
“…The Indonesian potato farmers generally save their seeds from the previous harvest (Fauzi, Baga, & Tinaprilla, 2016). The seeds are used several times because they could not afford new seeds (Ogola, Orawo, & Ayieko, 2012;Sayaka et al, 2012;Shafarina & Perdana, 2016). Thus, potato production is not optimum (Adiyoga et al, 2014;Mulyono et al, 2017;Wicaksana et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, imported garlic also has a shape and specifications that are superior to local garlic, so that consumers prefer imported garlic to local garlic [11]. This condition has further worsened Indonesia's national garlic production and cause Indonesia to become the largest garlic importer in the world [10,12].…”
Section: Introductionmentioning
confidence: 99%